SENYAWA GOLONGAN FLAVONOID PADA EKSTRAK n-BUTANOL KULIT BATANG BUNGUR (Lagerstroemia speciosa Pers.) - Astiti Asih, I. A. R.; Adi Setiawan, I M. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008)
Isolation and identification of flavonoid compounds from skin of Bungur (Lagerstroemia speciosa Pers.) have been conducted. Isolation was carried out by maceration and partition, to obtain n-hexane, ethyl-acetate, and nbutanol extracts. Concentrated n-butanol extract was purified using thin layer chromatography and column chromatography. Isolate F2.6 from n-butanol extract contains flavonoid compounds. Uilta Violete - Visible spectra showed that the flavonoid compounds were flavanon or dihidroflavanol, with characteristic wavelengths from 275 to 295 nm for Band II and 350 to 400 nm for Band I. Shifting reagents added indicated no hydroxyl group at C-3 and C-5, hydroxyl group at C-7, no ortho-dihydroxyl group at ring A,B, or C, and O-glycoside at C-7. Infrared spectra indicated characteristic functional groups of O-H bonded, CH alifatic, C=O, C=C aromatic, C-O, and CH aromatic. The flavonoid compounds indicated was flavanon group, which has functional groups of O-H bonded, CH alifatic, C=O, C=C aromatic, C-O, and CH aromatic, and hydroxyl group at C-7. It does not have ortho-dihydroxyl group at ring A,B, or C, but has O-glycoside at C-7.
Keywords: isolation, bungur, Lagerstroemia speciosa Pers., flavanon